Diagnostic Importance of Crystals in Woods of Family Anacardiaceae - Gupta, Sangeeta; Agarwal, Manisha (Indian Forester, 2006)
The paper describes the presence, absence, distribution pattern and location of crystals in 36 species of 19 genera, both native and naturalized, of the family Anacardiaceae from India. The study indicated that in view of their occurrence, location specificity and distinctive types, these features are helpful in wood identification of most of the species of this family.